THE IMPACTS OF ECONOMIC CRISIS ON FIRM-LEVEL INNOVATION IMPLEMENTATION: IMPLICATIONS FOR SUSTAINABLE DEVELOPMENT IN THE CONSTRUCTION INDUSTRY - Azubuike Anthony UGWUOKE; Carl ABBOTT (Journal of Construction Project Management and Innovation)
Innovation is viewed by many as a driving force for sustainable economic and social change. Indeed, it has often been argued that continuous innovation is essential for sustainable developments in the construction industry. However, it has been established that economic crises negatively impact firms’ capacity to implement innovations. The size of the effect and the impact on firm-level innovation differ widely across countries and industries. In the case of Nigeria, it has been argued that the rather frequent economic turbulence it experiences significantly affects firm-level innovation implementation in the local construction industry. This study identifies the key effects of economic crises on construction contractors and how these impact firm-level innovation implementations (it focuses on the factors at play in this regard). The paper provides an overview and synthesis of the literature on innovation, economic crisis, innovation persistence and sustainable development. This is supported by case studies and semi-structured interviews within construction contractors based in Abuja, Nigeria. The study finds several key effects of economic crises on construction contractors in Abuja Nigeria. These are shrinking demands for products and services, increased operating costs, increased delays in payments for jobs completed, increased difficulties in accessing credits and loans, declining revenue and profit levels, a rise in employee dissatisfaction and a surge in crime rate.